2009
DOI: 10.1590/s1516-89132009000100020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the accumulation of phosphate and magnesium ions in the yeast cells on the ethanol productivity in batch ethanol fermentation

Abstract: The accumulation of phosphate and magnesium in the yeast cells is not necessary to assure the ethanol productivity of batch ethanol fermentations. To avoid the decrease of the ethanol productivity it was sufficient to use a fermentation medium containing calculated concentrations of phosphorus and magnesium sources in order to maintain practically constant the phosphorus and magnesium initial contents of the biomass during the fermentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…This nutritional limitation had a pronounced effect on the experiments, leading to a significant reduction in yeast cell viability and fermentation inhibition [6,61]. Both phosphorus and nitrogen are essential for yeast activity and alcoholic fermentation [62,63] and directly affect cell viability during alcoholic fermentation [64]. Phosphorus constitutes an inorganic component of yeast cells, accounting for between 0.8% and 2.6% of their dry weight [65].…”
Section: Effects Of Wort Composition On Very High Gravity Fermentationmentioning
confidence: 99%
“…This nutritional limitation had a pronounced effect on the experiments, leading to a significant reduction in yeast cell viability and fermentation inhibition [6,61]. Both phosphorus and nitrogen are essential for yeast activity and alcoholic fermentation [62,63] and directly affect cell viability during alcoholic fermentation [64]. Phosphorus constitutes an inorganic component of yeast cells, accounting for between 0.8% and 2.6% of their dry weight [65].…”
Section: Effects Of Wort Composition On Very High Gravity Fermentationmentioning
confidence: 99%
“…Increased fermentation rate, cell viability and ethanol yield for both ale and lager yeast strains under normal (12°P) and high gravity (20°P) wort has been reported in the work of Rees and Stewart (1999) upon supplementation of 500 ppm Mg 2+ with best throughput for ethanol under oxygenated condition (Aleksander et al, 2009). Villen et al (2009) has shown that yeast cells requires a constant narrow range of magnesium amounts in other to sustain high ethanol productivity, rather than its excessive accumulation, which has been believed to be proportionate to fermentation efficiency. This proposition is supported by the report of Pironcheva (1998) that showed higher concentration (>700 µM) of magnesium levels, to have no further influence on ethanol yield.…”
Section: Role Of Magnesium In Ethanolic Fermentationmentioning
confidence: 99%
“…a estabilização das membranas das células de leveduras além de serem íons protetores em altas concentrações de etanol, principalmente quando submetidas a grandes variações do meio, como a pressão osmótica(COURCHESNE et al, 2011).Estes nutrientes são de fundamental importância em processos industriais que centrifugam a biomassa celular, havendo assim a perda de umidade. Os íons de fósforo e magnésio acumulados nas células de leveduras são importantes para a fermentação alcoólica(VILLEN et al, 2009).Para obter alta eficiência de produção de etanol por levedura, muitos fatores, como nitrogênio, oligoelementos, vitaminas e aeração foram investigados. O nitrogênio é um dos nutrientes essenciais para a fermentação do etanol, especialmente sob condições de VHG(BAI et al, 2008).…”
unclassified